Soccer training : games, drills and fitness practices - Whitehead, N. J.; Cook, Malcolm (London : A&C Black, 1994)
A handbook of basic soccer games and drills designed to enhance tactical and organizational skills as well as improve ball control and general fitness.
Adult
Keywords: Soccer -- Handbooks, manuals, etc; Soccer -- Rules; Soccer -- Handbooks, manuals, etc; Soccer -- Technique